The Efficacy of Polymer Coatings for the Protection of Electroless Copper Plated Polyester Fabric - Ojstršek, Alenka (Polymers (Basel), 2020)
The selective metallisation of textiles is becoming a very important process in the development of electronic or e-textiles. This study investigated the efficacy of polymer coatings for the protection of copper (Cu) conductive tracks electroless plated on polyester (PES) fabric against laundering and rubbing, without essentially affecting the physical-mechanical and optical properties of the base material. After the electroless deposition of a consistent layer of Cu onto PES, four polymers were applied individually by screen-printing or padding. The physical-mechanical characterisation of coated textiles revealed that polyurethane resin (PUR) and modified acrylate resin (AR) had little effect on the air permeability, tensile strength and breaking tenacity of the PES, as compared to silicone elastomer polydimethylsiloxane (PDMS) and epoxy resin (ER). On the other hand, PUR and PDMS had higher abrasion resistance and photo-stability under prolonged UV irradiation, as compared to AR and ER. In addition, freshly Cu plated samples were coated with polymers, washed up to 30 cycles and characterised by measuring their electrical resistivity, determination of colour changes and the examination of the surface morphology. Based on these results, PUR presented the most suitable protection of Cu tracks on PES, with the lowest impact on physical-mechanical properties. ER is not recommended to be used for protection of Cu tracks on fabrics, due to its rigidity, low photo-stability, washing and wear durability.